FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT SYNDROME PADA ANGGOTA POLISI SATUAN RESERSE KRIMINAL POLRES CIREBON KOTA DI MASA PANDEMI COVID-19 TAHUN 2020 - Akmalia Eka Lestari (2021)
Burnout syndrome is an excessive stress for an extended period and causes physical or mental fatigue. During COVID-19 pandemic the police have additional taks such as raid mask, crowd place, and COVID-19 health certificate that can cause burnout. The purpose of this study is to describe and discover the association between internal and external factors with burnout syndrome among Police Detectives in Cirebon Criminal Investigation Unit during the COVID-19 pandemic. This research used a quantitative analytical approach with a cross-sectional design study. This study's sample was 54 Police Detectives by using total sampling techniques. The data collected in this study was generated from Maslach Burnout Inventory questionnaires and through records and documents related to the Cirebon Investigation Unit. Based on the study results, 61,1% of respondents experienced a high level of burnout, and 38,9% with a low-level burnout. Bivariate analysis results with chi-square obtained two factors associated with burnout: workload factors (p-value=0.02) and social support (p-value= 0.01). Recommendations for the institution and the Police Detectives are to maximize work program of special unit dealing with psychosocial hazards, rewarding excellent employees regularly, and implementing relaxation regularly to manage stress and create a supportive surrounding environment.